Effects of grit on medical students’ wellbeing during clerkships: a longitudinal observational cohort study - Lin, Yung Kai; Lin, Chia-Der; Chen, Der-Yuan; Lin, Blossom Yen-Ju (Frontiers in Medicine, 2024)
In medical education, the clerkship phase is a demanding period during which medical students learn to navigate the responsibilities of medical school and clinical medicine. Grit, a personal quality regarded as a non-cognitive trait, refers to perseverance and passion; specifically, it represents the ability to endure hardship and work industriously toward a goal. Most studies analysed grit as a single concept and few studies have investigated the effect of grit on the well-being of medical students through the whole-specialty training (i.e. surgical and non-surgical specialty rotations) required in clinical clerkships. Therefore, this study investigated whether associations exist between medical students’ grit, measured by the two subconstructs of perseverance and passion, and their well-being during clerkships in surgical and non-surgical specialty units. This one-year prospective web-based questionnaire study enrolled fifth-year medical students at a tertiary medical centre in central Taiwan between September 2017 and July 2018 in their first-year clerkship. The students’ sex, age, and grit were measured at the start of their clerkship. Routine surveys were conducted over one year to assess burnout and compassion satisfaction for students’ well-being, and the training specialty characteristics of the surgical and non-surgical specialty departments were recorded. This study included 92 medical students and 1,055 survey responses from individual specialty rotations. Descriptive, univariate and multivariate analyses were performed. Our results revealed that medical students’ perseverance, as part of grit, was related to lower burnout and higher compassion satisfaction during clerkships, but not the subconstruct of passion. Moreover, the positive trait of perseverance measured in our study had greater explanatory power for compassion satisfaction than for burnout. Even though positive traits such as perseverance equipped medical students for compassion satisfaction, additional factors attributed to medical students’ burnout must be identified. Furthermore, the results revealed that older medical students suffered from less burnout than their younger counterparts, and that male medical students expressed higher compassion satisfaction than their female counterparts.